Discrimination of Arabic contrasts by American learners - Al Mahmoud, Mahmoud S. (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2013)
This article reports on second language perception of non-native contrasts. The study specifically tests the perceptual assimilation model (PAM) by examining American learners’ ability to discriminate Arabic contrasts. Twenty two native American speakers enrolled in a university level Arabic language program took part in a forced choice AXB discrimination task. Results of the study provide partial evi- dence for PAM. Only two-category contrasts followed straightforwardly from PAM; discrimination results of category-goodness difference and both uncategorizable contrasts yielded partial support, while results of uncategorized versus categorized contrast discrimination provided counter-evidence to PAM.
Keywords: discrimination of sound contrasts; Arabic consonant contrasts; perceptual assimilation model